Geoportale Nazionale: il Piano Straordinario di Telerilevamento per l'Ambiente - Costabile, Salvatore (GEOmedia, 2010)
Geoportale Nazionale: the remote sensing special plan for environment Due to its geomorphological conformation, the italian territory is subject to a high hydrogeological instability. For this reason the PST-A, enacted by MATTM, is aimed at empowering the capability of land observation by collecting high resolution remote sensing data. The multitemporal database, built from Lidar and Interferometric SAR data, is available through the Geoportale Nazionale. The web portal can provide and manage geographical informations of the whole Italian country, giving organizations a tool to organize soil protection activities